The use of the Ruthenian Languague in Ecclesiastical Books and its Relations to the Religious Identities in the Ruthenian Lands of the Grand Duchy of Lithuania in the 14 - 18th Centuries: the Protestant and Uniat Traditions - Temčinas, Sergejus (Lietuvos istorijos studijos, 2011)
-
Keywords: -